PEMBERDAYAAN PADA KELOMPOK BUDIDAYA IKAN WARNA TANI DALAM SEGI EKONOMI Nurul Hafizhah Sekarwangi1, Dedi Herdiana1 - Nurul Hafizhah Sekarwangi; Dedi Herdiana (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
The research entitled "Community Economic Empowerment in the Warna Tani Fish Cultivation Group in Mulyasari Village, Majenang District, Cilacap Regency. The researcher raised this issue because he wanted to know the economic empowerment of the community carried out by the Warna Tani fish farming group in Mulyasari Village. This type of research uses descriptive qualitative research methods using observation and interview techniques. The focus of the research is the empowerment of the Warna Tani fish farming group and the party who helps empower the Cilacap District Fisheries Service. The results showed that the implementation of empowerment was carried out in stages, processes, and strategies. In terms of income, members of the Warna Tani fish farming group experienced a significant increase compared to before joining the group. The Warna Tani fish farming group is experiencing obstacles such as the price of feed getting more expensive, the uncertainty of the weather which can disrupt the condition of the pond water. Members minimize obstacles by making traditional fish feed and protecting ponds from being directly exposed to rainwater.